Sinergitas Pemimpin Gereja Menuju Kepemimpinan Transformatif di Era Disruptif - Lizardo, Jimmy; Chendralisan, Lenny H. S.; Sumakul, Nicolien Meggy (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2024)
Synergistic leadership is one of the keys to success in building an organization. Despite the reality on the ground, a leader is generally still often associated with seniority or gender status. Still, in the current era of disruption, the stigma of leadership based on seniority and gender must be eliminated because today's leaders place more emphasis on personal competence. To achieve remarkable goals, church leaders must build leadership that synergizes with subordinates, such as church ministers. The synergy referred to here is the collaboration of leadership teams between generations and genders. This study aims to explore the benefits of leadership synergy in an organization and provide direction for leaders on building optimal leadership synergy. Use literature reviews (books and journals) to analyze leadership synergies, transformative leaders, and technological disruption. The author proposes several steps to build leadership synergy to be optimal, including shepherds, creating a clear framework regarding the duties and responsibilities of each leader; generations of leaders respect each other's roles and authorities, strengthen communication in an attitude of mutual respect, and respect; establish a shared vision, mission, and goals; Develop a culture of collaborative work between leaders. Abstrak Kepemimpinan yang sinergis merupakan salah satu kunci keberhasilan dalam membangun suatu organisasi. Sekalipun realita di lapangan, pada umumnya seorang pemimpin masih sering dikaitkan dengan status senioritas atau gender, namun di era disrupsi saat ini stigma kepemimpinan berdasarkan senioritas dan gender harus dihilangkan, karena soal pemimpin masa kini lebih ditekankan pada kompetensi pribadi. Untuk mencapai tujuan yang besar, pemimpin gereja perlu membangun kepemimpinan yang bersinergi dengan bawahannya dalam hal ini pelayan-pelayan gereja. Bersinergi yang dimaksud di sini adalah kolaborasi tim kepemimpinan antargenerasi; dan antargender. Penelitian ini bertujuan menggali manfaat sinergitas kepemimpinan dalam sebuah organisasi dan memberi arah bagi pemimpin bagaimana cara membangun sinergitas kepemimpinan yang optimal. Menggunakan kajian literatur (buku dan jurnal) untuk menganalisis sinergitas kepemimpinan, pemimpin transformatif dan disrupsi teknologi. Penulis mengusulkan beberapa langkah membangun sinergitas kepemimpinan agar optimal, di antaranya: gembala membuat kerangka kerja yang jelas mengenai tugas dan tanggung jawab masing-masing pemimpin; generasi pemimpin saling menghargai peran dan kewenangan masing-masing; memperkuat komunikasi dalam sikap saling menghormati dan menghargai; menetapkan visi, misi dan tujuan bersama; mengembangkan budaya kerja kolaboratif antar pemimpin.